Aortic rupture as a result of low velocity crush. Issue 4 (1st July 1999) - Reid, C; Livesey, S A; Egleston, C V
Abstract : A case of aortic disruption in a 35 year old lorry driver is described. This occurred as a result of a low velocity crushing force. Clinicians should be aware that this mechanism of injury may result in aortic disruption as well as the more commonly mentioned severe deceleration force.